KARAKTERISTIK BIODEGRADABLE FILM BERBASIS SELULOSA KELOBOT JAGUNG (Zea mays) DENGAN PENAMBAHAN GLISEROL DAN CARBOXY METHYL CELLULOSE (CMC) CHARACTERISTICS OF BIODEGRADABLE FILM BASED ON CORN HUSK (Zea mays) WITH THE ADDITION OF GLYCEROL AND CARBOXY METHYL CELLULOSE (CMC) - Prasetyo, Yusuf Eko; -, Zulferiyenni; Nurainy, Fibra; -, Susilawati (Jurnal Agroindustri Berkelanjutan, 2024)
Biodegradable film is a material similar to conventional plastic which is more easily degraded in nature. Corn husk contains 42.31% cellulose, which can be used for making biodegradable films. The purpose of this study was to determine the effect of the addition of glycerol and the addition of CMC on the characteristics of biodegradable films based on corn husk cellulose and to determine the effect of the interaction between glycerol and CMC on the attributes of biodegradable films based on corn husk cellulose. This study used two-factor, complete randomized block design and three replications. The first factor is the concentration of glycerol (1.5%, 2% and 2.5%). The second factor is CMC (2%, 2.5%, and 3%). The results showed that the concentration of glycerol and CMC significantly affected the tensile strength value, percent elongation, thickness, and water vapor transmission rate. The best results were obtained at a concentration of 2.5% glycerol and 2% CMC with a tensile strength value of 284.94 MPa, a percent elongation value of 27.53%, a thickness of 0.23 mm, and a water vapor transmission rate of 2.05 g/m²/day. Corn husk cellulose-based biodegradable film can be stored at room temperature for six weeks and decomposes in the soil for five weeks.